2011
DOI: 10.1007/s13197-011-0446-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and physical quality characteristics of Ghanaian cocoa beans as affected by pulp pre-conditioning and fermentation

Abstract: Investigations were conducted to evaluate the effects of pod storage (as a means of pulp preconditioning) and fermentation on the chemical composition and physical characteristics of Ghanaian cocoa beans. A 4×2 full factorial design with factors as pod storage (0, 7, 14, 21 days) and cocoa treatment (fermented and unfermented) were conducted. Samples were analyzed for their chemical composition (moisture, crude fat, crude protein, ash and carbohydrate content) and mineral content using standard analytical meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
79
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(112 citation statements)
references
References 29 publications
10
79
0
11
Order By: Relevance
“…Total and extractable zinc, manganese, copper and cobalt increased significantly (P≤0.05) when the grains flour was fermented for 14 days. Similarly, Afoakwa et al (2011) reported that fermentation significantly increased the copper content of the Ghanaian cocoa beans. The increment in HCl extractability of both major and trace minerals of corn genotypes is likely to be due to the reduction of antinutrients (phytate and polyphenols) as a result of fermentation during which phytase and tannase enzymes released during fermentation which hydrolyzed phytate and polyphenols, respectively.…”
Section: Resultsmentioning
confidence: 89%
“…Total and extractable zinc, manganese, copper and cobalt increased significantly (P≤0.05) when the grains flour was fermented for 14 days. Similarly, Afoakwa et al (2011) reported that fermentation significantly increased the copper content of the Ghanaian cocoa beans. The increment in HCl extractability of both major and trace minerals of corn genotypes is likely to be due to the reduction of antinutrients (phytate and polyphenols) as a result of fermentation during which phytase and tannase enzymes released during fermentation which hydrolyzed phytate and polyphenols, respectively.…”
Section: Resultsmentioning
confidence: 89%
“…Afoakwa et al (2012) and Camu et al (2008) reported that 37 fermentation of fresh cocoa beans contributed to a decrease in 38 flavan-3-ol content as well as a reduction in the level of bitterness 39 and astringency in the final product. 40…”
mentioning
confidence: 99%
“…Indeed, the highest value of moisture content found in Vietnamese cocoa bean is only 6.99% (TD6), while that value of Ghanaian cocoa bean quadruple. Noticeably, the ash content of Vietnamese cocoa beans (2.5-3.7%) is considerably high compared to Ghanaian cocoa beans ash content (2.3-3.5%) (Afoakwa et al, 2013). This proves that Vietnamese cocoa is rich in minerals since the ash property indicates minerals content.…”
Section: Chemical Composition Analysis 321 Moisture and Ash Contentmentioning
confidence: 85%
“…2), this shows that these values are not significantly different. At this point, the protein level of Vietnamese cocoa beans is slightly lower compared to Nigerian and Ghanaian cocoa bean protein level (Nigerian cocoan beans 17.5% (Aremu et al, 1995), Ghanaian cocoan beans 18.8% (Afoakwa et al, 2013). …”
Section: Crude Protein Contentmentioning
confidence: 85%
See 1 more Smart Citation